(untitled) (Research, Society and Development, 2022)
What is the origin of psychic sufferings revealed with intensity in capitalist sociability? From this question, the general objective of this article was formulated: to understand the genesis of psychic sufferings in capitalist sociability and specific objectives: 1) to demonstrate the psychic sufferings from the work "the malaise in civilization" of Freud; 2) relate the psychic sufferings with the category "strange work" developed by Marx and present the associated work as a way to overcome the malaise of society. As a methodological procedure, the investigation of the object was carried out based on a qualitative research of the bibliographic type. For its development, the theoretical contributions of Freud (1996), Marx (2004), among others, were used. The results of the research were: psychic sufferings are the fruit of the development of the dialectical relationship between objectivity and subjectivity and the overcoming of these sufferings can only occur through a free and associated sociability.